The Effect of Accrual-Based Government Accounting Standards Implementation on the Quality of Financial Reporting with Regional Apparatus Organizational Commitment as a Moderating Variable in Serdang Bedagai Regency Government - Juni Yanti Napitupulu; Dito Aditia Darma Nasution; Agus Tripriyono (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to examine the determinants of accrual-based Government Accounting Standards (GAS) implementation and to empirically test the role of Organizational Commitment of Regional Government Organizations (Organisasi Perangkat Daerah/OPD) as a moderating variable in the context of local government. The study was conducted across 30 OPDs in Serdang Bedagai Regency and involved 180 financial management officers as respondents. A quantitative approach was employed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that Human Resources, Supporting Facilities, Compliance with Laws and Regulations, Government Internal Control System (GICS), Understanding of Accrual-Based GAS, Employee Motivation, and Manual Application of Accrual-Based GAS have positive and significant effects on the implementation of accrual-based GAS. The structural model demonstrates strong explanatory power, with an R² value of 0.762, indicating that 76.2% of the variance in accrual-based GAS implementation is explained by the variables included in the model. Organizational Commitment exhibits the strongest direct effect and serves as the most dominant predictor in the model. Furthermore, the moderation analysis reveals that Organizational Commitment significantly strengthens most of the relationships between the independent variables and accrual-based GAS implementation, except for one non-significant moderating relationship. This finding suggests that the moderating role of Organizational Commitment is selective and context-dependent, as certain aspects of accrual-based GAS implementation are more strongly influenced by individual capacities of public officials—such as technical competence, intrinsic motivation, and work experience—than by organizational structural factors. This study contributes to the public sector accounting literature by demonstrating that Organizational Commitment functions as a strategic integrator that aligns individual, technical, and regulatory factors in achieving accountable and accrual-based local government financial management